ANALISIS KOMITMEN PROFESIONAL GURU DI INDONESIA MENGGUNAKAN RASCH - Rais Hidayat; Yuyun Elizabeth Patras (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2021)
Abstract. The goal of this research is to find an instrument that is able to accurately measure the teacher's professional commitment variable as well as provide recommendations to improve it. This research design uses quantitative research with data acquisition through research instruments filled by 449 teachers from the territory of Indonesia through purposive sampling method and data analysis technique using Rasch Modeling. The research instrument before being used was first assessed by experts (expert judgment) and tested on 10 teachers. The reseach found: (1) There were 10 statement items that were proven to be able to accurately measure the teacher's professional commitment variable; (2) Some actions are recommended to increase teacher professional commitment: (i) encourage teachers to commit to completing tasks that exceed the standards set by the school; (ii) encourage teachers to be more actively involved in teacher professional activities; (iii) encourage teachers to internalize school values; (iv) encourage teachers to complete all tasks in school; and (v) encourage teachers to have the ability to adapt to various changes in education.Keywords: professional commitment, Rasch Modeling, teacher commitment Abstrak. Tujuan penelitian ini untuk menemukan sebuah  instrumen yang mampu secara tepat mengukur variabel komitmen profesional guru  sekaligus memberikan rekomendasi untuk  meningkatkannya. Rancangan penelitian ini menggunakan penelitian kuantitatif dengan pemerolehan data  melalui instrumen penelitian yang diisi oleh 449 guru dari wilayah Indonesia melalui metode purposive sampling dan teknik analisis data menggunakan Pemodelan Rasch. Instrumen penelitian sebelum digunakan terlebih dahulu mendapat penilaian dari ahli (expert judgement) dan  diujicobakan terhadap 10 guru. Penelitian menemukan: (1) Ditemukan 10 butir pernyataan yang terbukti mampu mengukur dengan tepat (fit) variable komitmen profesional guru; (2) Direkomendasikan beberapa tindakan untuk peningkatan komitmen profesional guru: (i) mendorong guru untuk berkomitmen menyelesaikan tugas yang melebihi standar yang ditetapkan sekolah; (ii) mengupayakan para guru untuk lebih terlibat aktif dalam kegiatan profesional guru; (iii) mendorong guru untuk menginternalisasi nilai-nilai sekolah; (iv) mendorong guru dapat menyelesaikan semua tugas di  sekolah: dan (v) mendorong guru untuk memiliki kemampuan beradaptasi dengan berbagai perubahan dalam pendidikan. Kata kunci: komitment profesional, Rasch Model, komitmen guru